Upaya Peningkatan Motivasi dan Hasil Belajar Kognitif Mahasiswa Program Studi Biologi STKIP Pembangunan Indonesia Melalui Model Pembelajaran Grup Investigasi dan Model Pembelajaran Inkuiri Pada Matakuliah Anatomi dan Fisiologi Manusia - Muh. Rilzadi Trias Jaya Putra Nurdin (Universitas Islam Negeri Mataram, 2017)
This study was a quasy experiment that aims to investigate and compare students' cognitive learning outcomes using two different learning model i.e. investigation learning and inquiry learning. The third year students of biology class VIg and VIh were involved in experimental groups, class VIg experienced investigation learning model and class VIh was implementing inquiry learning model. Both classes were taught Anatomy and Human Physiology courses. Data were collected by administrating questionnaire sheets for learning motivation and pretest-postest for cognitive learning result. This result showed that the inquiry learning model improved the motivation and cognitive learning outcomes in one experimental group (Class VIh). It was shown by the mean score was 61.40 for inquiry learning model and 48.40 to the investigation learning model. To summarize this study, inquiry learning model had significant impact in students’ cognitive learning outcomes.